Epiphytic Lichens of Alacam Mountains Blackpine Forest (Balikesir - Kutahya) - ÖZYİĞİTOĞLU, GÜLŞAH; SEVGİ, ECE; SEVGİ, ECE; Sevgi, Orhan; TECİMEN, Hüseyin Barış; YILMAZ, Osman Yalçın; Acikgoz, Birkan (My University, 2011)
This study was conducted at pure Anatolian black pine (Pinus nigra Arnold subsp. pallasiana (Lamb.) Holmboe) forests of Alacam Mountains (Balikesir-Kutahya) in order to investigate the lichen species on black pine. 471 trees from 95 sample plots were sampled and a total of 37 epiphytic lichen taxa were recorded on barks. 15 taxa are new records for the province of Balikesir and 19 taxa for the province of Kutahya.